2019
DOI: 10.1109/access.2019.2946917
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Emergent Vegetation Effects on Manning’s Coefficient of Gradually Varied Flow

Abstract: Based on mechanical derivation, a new formula showing the effects of emergent vegetation on Manning's coefficient was established for complex gradually varied flow affected by rigid unsubmerged vegetation in open channels. The new formula indicates that the Manning's coefficient is a quadratic sum of its vegetal and boundary components with coefficients related to vegetation parameters. The variation characteristics of the total Manning's coefficient and its vegetal component calculated by the new formula were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Where it raised upstream the vegetated reach then it lowered within it and gradually backed to the normal depth downstream the vegetated reach. This observation agreed with the previous studies [10][11][12][13][14][15]. From this result, it can say that sided vegetation acts as an obstacle to the flow, causing an increase in the flow resistance upstream it, thus the water depth increased.…”
Section: Results and Analysis 41 Effect Of Bank Vegetation On Water S...supporting
confidence: 92%
See 1 more Smart Citation
“…Where it raised upstream the vegetated reach then it lowered within it and gradually backed to the normal depth downstream the vegetated reach. This observation agreed with the previous studies [10][11][12][13][14][15]. From this result, it can say that sided vegetation acts as an obstacle to the flow, causing an increase in the flow resistance upstream it, thus the water depth increased.…”
Section: Results and Analysis 41 Effect Of Bank Vegetation On Water S...supporting
confidence: 92%
“…It concluded that for the same discharge, the vegetation density has a direct relationship with the water depth upstream of the vegetated reach. [14,15] experimentally studied the effect of rigid vegetation distributed in a channel's bed on water level and concluded that the water level rose upstream of the vegetation patch and then lowered through it. [15] Proposed a water surface slope equation in terms of vegetation density as follows;…”
Section: Introductionmentioning
confidence: 99%
“…To study the transport of water in the drainage channels formed in the model according to the soil characteristics in the region of interest, different values of Manning Coefficient were adopted. The Manning Coefficient seeks to reflect the roughness of the channel and its interference with the water flow (ZHANG et al, 2019). The values used in this study were taken from Gribbin (2014) on pages 390, 391 and 392.…”
Section: Methodsmentioning
confidence: 99%
“…It is also worth pointing out that some authors, in case of channels with emergent rigid vegetation, have directly focused on the Manning or Darcy-Weisbach coefficient instead of considering the dependence of the resistance to flow on C D [48][49][50].…”
Section: Overview and Basic Definitionmentioning
confidence: 99%